Planning of Concrete Structure on the Upper Building of Air Traffic Tower with Special Moment Bearing Frame System Method in Pohuwato Airport Project, Gorontalo Province - Wahyu Diyano Aryana, I Gde; Wasito, Bambang; Meilawati Eka Putri, Karina (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Currently, the Pohuwato Airport Project does not have plans to build an Air Traffic Tower facility. The Air Traffic Tower facility has an important role in monitoring the security and safety of Air Traffic and Road Traffic when the Pohuwato airport is operating, because this requires an Air Traffic Tower Construction Plan at Pohuwato Airport, Gorontalo Province, which can withstand high earthquake conditions. . Planning for the superstructure of an air traffic tower includes planning of plate, column and beam structures which will later be used for preliminary design planning, structural modeling, structural loading using the Special Moment Resisting Frame System (SRPMK) method using the SAP2000 application, work planning, and calculation of plans Cost Budget (RAB). The preparation of this final project results obtained from the calculation of the structure of the building, namely the main beam reinforcement dimensions 50 x 70 cm, with 10 D 19 flexural reinforcement at positive moments, 12 D 19 flexural reinforcement at negative moments. Reinforcement of joists with dimensions of 20 x 30 cm, with 2 D 13 bending reinforcement at positive moments, 3 D 13 bending reinforcement at negative moments. Floor slab dimensions 300 cm x 300 cm, with 5 D19 flexural reinforcement at positive moments, 7 D19 flexural reinforcement at negative moments. Column dimensions 50 x 50 cm 12 D 19 flexural reinforcement and 2 P 10 – 150 mm stirrup reinforcement. As well as the calculation of the required Budget Plan (RAB) of Rp. 176.330.877.25 (spelled out One Hundred Seventy Six Million Three Hundred Thirty Thousand Eight Hundred Seventy Seven point Two Five Rupiah) for a concrete structure project in a building on the construction of a traffic tower.